2002
DOI: 10.1046/j.0021-8790.2001.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed cost of reproduction and senescence in the willow tit Parus montanus

Abstract: Summary 1.We studied age-specific survival rates in the willow tit Parus montanus in northern Finland using 15 years of capture-recapture data obtained from birds during the breeding seasons 1986-2000. In addition, short-and long-term costs of reproduction were investigated by comparing survival probabilities of breeding and non-breeding individuals. 2. We did not find evidence supporting age-specific survival probabilities in males. However, in females there was a significant decline in survival after the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 42 publications
(83 reference statements)
5
65
1
1
Order By: Relevance
“…As a corollary of this, it has recently been shown that when faced with an artificial life-threatening risk during reproduction, individuals from species with high survival and low fecundity reacted by changing their behaviour to reduce risks to themselves, whereas individuals from low survival-high fecundity species would expose themselves to a higher risk to decrease the risk to their offspring (Ghalambor & Martin 2001;Martin 2002). Reducing the risks associated with breeding activity might be particularly important for young individuals for two reasons: they probably incur disproportionately high costs of breeding through reduced survival, as suggested in two recent studies (Tavecchia et al 2001;Orell & Belda 2002), and they may experience comparatively lower reproductive output (Green 2001;Magrath 2001). Thus, long-lived cooperative (or non-cooperative) species should be particularly reluctant to breed in suboptimal habitats or under suboptimal conditions, as indicated by several correlative studies (Emlen 1990;Koenig et al 1992;Komdeur et al 1995;Frederiksen & Bregnballe 2001;Ekman et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As a corollary of this, it has recently been shown that when faced with an artificial life-threatening risk during reproduction, individuals from species with high survival and low fecundity reacted by changing their behaviour to reduce risks to themselves, whereas individuals from low survival-high fecundity species would expose themselves to a higher risk to decrease the risk to their offspring (Ghalambor & Martin 2001;Martin 2002). Reducing the risks associated with breeding activity might be particularly important for young individuals for two reasons: they probably incur disproportionately high costs of breeding through reduced survival, as suggested in two recent studies (Tavecchia et al 2001;Orell & Belda 2002), and they may experience comparatively lower reproductive output (Green 2001;Magrath 2001). Thus, long-lived cooperative (or non-cooperative) species should be particularly reluctant to breed in suboptimal habitats or under suboptimal conditions, as indicated by several correlative studies (Emlen 1990;Koenig et al 1992;Komdeur et al 1995;Frederiksen & Bregnballe 2001;Ekman et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that in this review, we reported opposite results in terms of reproductive costs in two populations of the same species, the willow tit (Parus montanus). In one of them, survival costs of reproduction have been detected [31], but not in the other one [63]. Whether these two populations differ in their level of paternal care, polygyny or pace of life, and whether these differences are translated into different costs of reproduction, remain to be explored.…”
Section: Tests Of Direct Costs Of Reproduction In Malesmentioning
confidence: 99%
“…However, contrasting patterns can sometimes emerge when senescence is investigated jointly in males and females. For instance, in willow tits (Parus montanus), early reproduction and survival in late life are independent in males, whereas females that do not breed during early life survive better in late life [18]. Overall, this emphasizes the need to test evolutionary theories of ageing in both sexes to identify the nature of the reproductive costs that influence performance in late life, and then the evolution of sex-differences in ageing patterns (see §4b for a specific discussion on this topic).…”
Section: (C) Late-life Traitsmentioning
confidence: 99%